First Record of Bipalium indicum (Whitehouse, 1914) and Bipalium bengalensis (Bhakat, 2020) in Nepalgunj Sub-Metropolitan City, Nepal (Voice: A Biannual & Bilingual Journal, 2025)
Numerous planarian species showing a significant phenotypic diversity have been documented to exist in different countries, but there are no documented reports about Bipalium in Nepal. In this paper, I presented the first report on the occurrence of Bipalium species in Nepal. The collected flatworm species were identified based on external morphological characteristics. Body length, body colour, the shape of the head, and the presence of longitudinal stripes on the dorsal side of the body were considered key for species identification. The description of the hammer-headed land flatworm Bipalium serves as the foundation for the current paper. Two species of Bipalium i.e., Bipalium indicum and Bipalium bengalensis were identified from the Nepalgunj sub-metropolitan city of Banke district, Nepal at 28°2′53.39′′N and 81°37′17.48′′E. The species identified are new to Nepal and have not ever been documented.